Praktikum Mekanisme Listrik Dalam Pembelajaran Fisika SMP oleh Mahasiswa S1 UIN Sultan Syarif Kasim - Dandi Inplant Guspandi; Rian Vebrianto (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
The purpose of making this article is to find out the deepening of the material about electrical circuits, the workings of electrical circuits, as between modules with the purpose of the practicum that has been done. This type of research is used by using literature studies and direct practices carried out in the Science Education laboratory room. The subjects used by them are students majoring in semester 2 Science Education University of Sultan Syarif Kasim Riau. The results of the research are the number of students who do not understand about the electricity practices that discuss modules because of the large number of vocabulary that is not understood by students. For this reason, it is necessary to increase the practicum in the future, especially in the module, using language that is easily understood by students and students, and also with a guide who understands what he teaches practicum compilation.